FACTORS THAT INFLUENCE PROFIT GROWTH IN RETAIL TRADING COMPANIES - Wahyu Indah Mursalini; Esi Sriyanti; Arma Febriana (Program Studi Manajemen Fakultas Ekonomi Universitas Palembang, 2024)
This research aims to analyze the influence of economic growth and stock prices on profit growth in companies in the retail trade sub-sector. The number of samples in this research was 20 Retail Trading companies registered on the Indonesia Stock Exchange using the Purposive Sampling. The type of data used in this research is quantitative. Based on the results of statistical analysis, it can be concluded that Economic Growth has a significant effect on Profit Growth in the companies studied. It is indicated by the results of the t-count test 2.590 > t-table 1.664, significance 0.011 < 0.05. So it can be concluded that Economic Growth influences Profit Growth. Based on the results of statistical analysis, it can be concluded that share prices do not have a significant effect on profit growth in the companies studied. This is indicated by the results of the t-count value -1.041 < t-table 1.664 and a significance of 0.301 > from a significance level of 0.05. So it can be concluded that the Share Price variable does not have a significant effect on Profit Growth. Economic Growth and Stock Prices significantly influence Profit Growth. This is proven by using the f test with a significance value of 0.023 < 0.05 and f- count 3.949 < f-table 3.112. This can be seen from the R Square value of 0.091 or 9.1% while the remaining 90.9% is influenced or explained by other variables not examined in this research such as Net Profit Margin, Return On Assets and Debt To Equity Ratio which are not caused by in this research.